Diabetes mellitus and associated factors among psychiatric patients receiving antipsychotic treatment at Wachemo University Nigist Elleni Hospital, South Ethiopia - Amanuel Melaku Laemango; Misgana Bekele Begna; Dembelo Tirago Masebo; Dilebo Lefebo Anshebo; Shifarew Bekele Woyesa; Mengistu Lodebo Funga (PLoS ONE, 2025)
Background Diabetes mellitus is one of the most common non-communicable diseases, and its epidemic proportion has placed it at the forefront of public health challenges currently facing the world. Patients with severe mental illnesses who receive antipsychotic treatment have a high risk of developing metabolic disturbances. Method and material A hospital-based cross-sectional study was conducted. A total of 216 psychiatric patients on treatment were included and selected by consecutive convenient sampling techniques. An interviewer-administered questionnaire was used to collect socio-demographic, clinical, and behavioral characteristics. The levels of fasting blood glucose were measured by Cobas 4000 series Cobas c311Basel, Switzerland. The data were entered into Epi data version 4.6 and analyzed by SPSS version 25. Data were summarized by tables, graphs, and descriptive statistics. Bivariate and multivariate logistic regressions were used. P-value <0.05 was considered statistically significant. Result A total of 216 psychiatric patients were enrolled in this study. The overall prevalence of diabetes mellitus was 25(11.6%). Among participants with diabetes mellitus, the prevalence of diabetes mellitus was higher in females than males (17(68.0%) vs 8(32.0%). Female (AOR:6.483, 95% CI (1.647, 25.516), P- value = 0.007), longer duration of antipsychotic use (AOR: 7.876 (1.587–39.090), moderate physical activity (AOR: 0.220, 95% CI (.057-.85), P- value = 0.028), higher body mass index (11.869, 95% CI (2.188–64.374), P- value = .004), and high cholesterol(AOR:13.742. 95% CI (3.153–59.887), P- value = .000) were significantly associated to diabetes mellitus. Conclusion The finding of this study revealed that the prevalence of diabetes mellitus was 11.6%. Female sex, longer duration of antipsychotic use, moderate physical activity, overweight BMI, and high total cholesterol were significantly associated. Therefore, Health providers should regularly weigh patients and monitor long-term side effects of medication.